2015
DOI: 10.1093/jjco/hyv039
|View full text |Cite
|
Sign up to set email alerts
|

A new prognostic index for overall survival in malignant pleural mesothelioma: the rPHS (regimen, PS, histology or stage) index

Abstract: Objective: Existing prognostic indices for malignant pleural mesothelioma do not incorporate the recent advances in oncology care. The purpose of this study was to provide a prognostic index for overall survival in malignant pleural mesothelioma patients treated with chemotherapy with pemetrexed or best supportive care in the recent clinical setting. Methods: A retrospective cohort study was performed in two hospitals in Japan . The primary outcome was overall survival. The Cox proportional hazards model was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Previous studies have demonstrated that the epithelioid subtype is associated with more favorable survival outcomes compared to non-epithelioid subtypes [1, 37, 38]. We found that cSBL had strong cytotoxic effects in a broader range of mesothelioma cell types including pemetrexed- or cisplatin-resistant cells.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have demonstrated that the epithelioid subtype is associated with more favorable survival outcomes compared to non-epithelioid subtypes [1, 37, 38]. We found that cSBL had strong cytotoxic effects in a broader range of mesothelioma cell types including pemetrexed- or cisplatin-resistant cells.…”
Section: Discussionmentioning
confidence: 49%
“…In our study, patients who had clinical benefit with first-line chemotherapy showed a 10 month improvement in median overall survival. Unlike a study by Kataoka et al 14 study, factors associated with a clinical benefit from chemotherapy were also evaluated in our study. Better PS, epithelioid histology and increased number of lymphocytes were associated with clinical benefit from first-line of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, histological type, stage, PS, and age were regarded as important confounding factors associated with OS (20,24), and they were considered in the analyses. Whether patients received platinum-based palliative chemotherapy in combination with pemetrexed was also considered in the analyses.…”
Section: Univariate and Multivariate Analyses Of Variables Associatedmentioning
confidence: 99%
“…Of the 86 patients treated with palliative chemotherapy, 68 (79.1%) died during the follow-up period. According to a previous report, histological type, stage, PS, and age were considered in the multivariate analysis (20,24). Whether patients received platinum-based palliative chemotherapy in combination with pemetrexed was also considered.…”
Section: Univariate and Multivariate Analyses Of Variables Associatedmentioning
confidence: 99%